Development of Basic Pencak Silat Techniques for High School Students - Wiguno, Lokananta Teguh Hari; Kurniawan, Ari Wibowo; Wahyudi, Heri; Puspitasari, Dianti Fera; Salamuddin, Norlena (Journal of Sport Science and Education, 2024)
Pencak silat is one of popular martial art originated from Indonesia that is learnt by students from various level.  The learning process of pencak silat requires innovative media to help students learn it effectively. This study aims to develop an application-based learning media as a suitable solution to overcome problems related to PSHT martial arts learning material for the Persaudaraan Setia Hati Terate (PSHT) club at high schools. This study employed a research and development (R&D) methodology. The participants were 17 pencak silat student-athletes from the PSHT club or extracurricular program. Observations and interviews were conducted to collect the data. This research completed three expert validations, which include evaluations by coaching experts with an average score of 83.0%, PSHT material experts with an average score of 83.25%, and media experts with an average score of 97.5%. The overall product trial involved 17 student-athletes and was split into two phases: a small group trial with 5 participants, which achieved an 84.58% success rate, and a large group trial with 12 participants, which yielded an 80.90% success rate. Based on these results, the learning media for basic pencak silat techniques for PSHT student-athletes met valid standards and may be used without revision.